THE INFLUENCE OF SELF CONTROL AND FAMILY ENVIRONMENT AGAINST MORAL DEGRADATION AT THE AGE OF SCHOOL - azkiya maisari; Holilulloh Holilullah; Muhammad Mona Adha (FKIP Unila, 2012)
The implementation of this research was meant to explain the influence of self control and family environment against moral degradation at the age of schools in MTs Nahdlatul Ulama Kaliawi Tanjungkarang Pusat Bandar Lampung academic years 2012-2013. Methods used in this research is a method of descriptive correlational. Population in this research is students mts nahdlatul ulama tanjungkarang lampung academic year 2012 / 2013 with the number of 66 people of respondents as sample of the population with the number of 30 people. Data in this research are collected through questionnaire, and documentation. the engineering data analysis using formulas a coefficient contingency or chi quadrat. The result showed that: (1) there are the influence of self-control against moral degradation at the age of school in the class VIII MTs Nahdlatul Ulama Tanjungkarang academic year 2012-2013. The influence of self-control against moral degradation at the age of school in the class VIII was in the category of strong. (2) there are environmental influences families to moral degradation at the age of school in the class VIII MTs Nahdlatul Ulama Tanjungkarang academic year 2012-2013. Environmental influences families to moral degradation at the age of school in the class VIII was in the category of strong.Keywords: self-control, family environment, moral degradation